Development of the document management system architecture - Осідач, Андрій Олегович (Technology audit and production reserves, 2014)
Document management is a process of the document creation, distribution and deletion within an organization. Document management encompasses the processes and procedures business organizations use to capture, store, secure and retrieve information on a daily basis. For many organizations, these processes can be greatly improved with the use of document management system. The benefits of using DMS include: improved productivity, economic effect, improved management services, better access and use of information. Document management contains the following characteristics and all of them have been highlighted as system requirements: the subsystem that allows loading of information (documents), storage and archiving methods for files and documents, indexing subsystem, search tool for finding and retrieval of information, workflows for tracking of the life-cycle of a document and the workflow subsystem that allows the automatic routing of documents to responsible person, ability to support and administer system with different privileges and a subsystem of document versioning. The following results of the research were obtained: a description of the main purposes, analysis of existing software solutions, their advantages and disadvantages, main problems and innovative approaches that are necessary for system implementing. According to the outlined results, an efficient architecture of electronic documents has been developed. New modules that have been added to the traditional architecture highlight new scientific approaches based on the results of the research: Document clustering module aimed at automatic identifying of executor; Module performance analyzer instrument, the purpose of which is the automatic generation of the related documents chain and control of their execution.